Frequências de suplementação para ovinos de corte em pastos de Capim-Massai - Freitas, Alana Santos de (2021)
The objective of this study was to evaluate the effect of the frequency of concentrated supplementation on intake nutrient digestibility and performance of beef sheep grazing Panicum maximum cv. Massai. Thirty-six crossbred Santa Inês sheep were used, 18 males and 18 females with average initial weight of 17.0 ± 1.5 kg and average initial age of 90 ± 10 days grazing from 8:00 am to 4:00 pm and receiving supplementation concentrated in three frequencies: SD (daily supplementation); DA (supplementation every other day) and S2D (supplementation every other day). The experimental period lasted 120 days, with 20 days for adaptation and 100 days for data collection. The animals were weighed every 14 days to monitor the average daily and total weight gain and adjust the concentrate supply. To estimate the voluntary dry matter intake a combination of an external (LIPE®) and an internal (FDNi) indicator was used. A completely randomized design was used in a 2 x 3 factorial arrangement. There was no effect of the sex × frequency of supplementation interaction. Feed conversion was higher in females and between frequencies in animals supplemented every two days. There was no difference in dry matter intake however it was observed that animals supplemented every two days had higher intakes of pasture and neutral detergent fiber. In dry matter digestibility higher values were found in the daily and alternating frequency. There was no statistical divergence in neutral detergent fiber digestibility. Animals fed with daily and alternating supplementation showed higher frequencies in concentrate consumption when compared to the frequency every two days having consequently greater gains in average daily and total weight and greater final weight. Females had higher final weight compared to males. Sheep managed on massai grass pasture can be supplemented daily or on alternate days without affecting performance. Supplementation every other day is not recommended.